Paul’s Heart as Spatial Metaphor in 2 Corinthians - Pereira-Delgado, Álvaro (The Biblical Annals, 2024)
In 2 Cor 6:11–13, Paul states that his heart has been enlarged to welcome the Corinthians and urges them to reciprocate—although an insightful article by Christopher Land in ZNW has recently questioned this standard exegesis, which we will discuss. In 2 Cor 6:11–7:4, which functions as a peroratio of the preceding argumentation, Paul associates terms of body language (στόμα, καρδία, σπλάγχνα) with verbs of spatial meaning (πλατύνω, στενοχωρέω, χωρέω). Paul’s heart also appears in the letter as a spatial metaphor for his relationship with God ( 1:22; 3:2–3; 4:6). In our research, we will examine whether there could be a correlation between the horizontal dimension of the metaphor (Paul’s heart as a welcoming space for the Corinthians) and the vertical one (Paul’s heart as a place of encounter with God). Additionally, the heart serves Paul to establish the map of relationships in which his opponents are excluded because they boast ἐν προσώπῳ and not ἐν καρδίᾳ (5:12). In conclusion, drawing on the cognitive analysis of metaphors, we will try to highlight the semantic and pragmatic possibilities of Paul’s heart as a spatial metaphor in 2 Corinthians.